A COLOR THAT COMMUNICATES WITHOUT A WORD – “WHITE” - Sharma, Shivani; Bharti, Vandana (International Journal of Research -GRANTHAALAYAH, 2014)
The meaning of color white is purity, innocence, wholeness and completeness. It is the color produced by the combination of all the colors of visible spectrum.The color white belongs to ancient history. During the Paleolithic age, the artists used calcite and in chalk in their paintings. Egyptians connected it with their goddess Isis,who only dressed in white linen and hence used to wrap mummies.White was often associated with mother’s milk, in Greek mythology .White is the color of the human eye sees when it senses light which contains all the wave lengths of the visible spectrum. Mostly white animals have their color as a form of camouflage in winter such as dove,ivory gull,swans,arctic fox, white pearls produced by mollusk and when talking of its horrifying side it symbolizes ghosts and phantoms in many cultures/civilization. In India, white is worn on various rituals and often associated with sadness especially when somebody dies. Unlike other things, white also plays an important role in our diet.White is associated with the top of the color spectrumand, inAsian medicine, with strengthening to the lungs and large intestines .White fruits and vegetables contain nutrients such as beta-glucans, EGCG, SDG, and lignans that provide powerful immune boosting activity. These nutrients also activate natural killer B and T cells, reduce the risk of colon, breast, and prostate cancers, and balance hormone levels, reducing the risk of hormone-related cancers.White foods are often rich in sulfur and Quercetin. May reduce the risk of cancer and help the body get rid of cancer causing chemicals.e.g. buckwheat, cauliflower ,coconut, garlic, green onion, millet,mushrooms, sunflower seeds, tofu, white beans, corn, white eggplant, white radishes.